Ligature of the Left Main Coronary Artery after Surgery in Kawasaki Disease: Case Report - Barca,Laura Varela (2019)
Abstract We report a case of a 23-year-old man who was diagnosed with Kawasaki disease that progressed to a coronary aneurysm in the left main coronary artery (LMA). He had suffered from acute coronary syndrome and then underwent an emergent percutaneous coronary angioplasty, in which a polyurethane-covered stent was placed inside the aneurysm. The stent was thrombosed one year later, despite the patient had been treated with anticoagulant and antiplatelet therapy. Emergency percutaneous intervention was then performed. LMA was reopened and stent malposition was observed. Therefore, urgent coronary bypass grafting was performed in which a high degree of competitive flow was observed through the reopened stent. LMA was ligated at the inflow of the aneurysm, resulting in an improvement of graft flow. Left main ligature has not been previously reported.